2012
DOI: 10.1175/jcli-d-11-00443.1
|View full text |Cite
|
Sign up to set email alerts
|

Causes of the Rapid Warming of the North Atlantic Ocean in the Mid-1990s

Abstract: In the mid-1990s, the subpolar gyre of the North Atlantic underwent a remarkable rapid warming, with sea surface temperatures increasing by around 18C in just 2 yr. This rapid warming followed a prolonged positive phase of the North Atlantic Oscillation (NAO) but also coincided with an unusually negative NAO index in the winter of 1995/96. By comparing ocean analyses and carefully designed model experiments, it is shown that this rapid warming can be understood as a delayed response to the prolonged positive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
210
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(253 citation statements)
references
References 75 publications
43
210
0
Order By: Relevance
“…The observed differences between the warm phase and the cold phase of the AMV have shown warmer summer SATs over C-E Europe to be associated with a warm phase of the AMV and vice versa (Sutton and Hodson 2005;Sutton and Dong 2012). Similar results are found for the transition from a cold phase to a warm phase in the 1920s ) and the transition from a warm phase to a cold phase in the 1960s during the North Atlantic cooling Robson et al 2012). These studies also showed, during the warm phase of AMV, a positive summer precipitation anomaly over northern Europe including the BE region, thus suggesting a close association between the multidecadal variations of C-E European SATs and BE precipitation in summer.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The observed differences between the warm phase and the cold phase of the AMV have shown warmer summer SATs over C-E Europe to be associated with a warm phase of the AMV and vice versa (Sutton and Hodson 2005;Sutton and Dong 2012). Similar results are found for the transition from a cold phase to a warm phase in the 1920s ) and the transition from a warm phase to a cold phase in the 1960s during the North Atlantic cooling Robson et al 2012). These studies also showed, during the warm phase of AMV, a positive summer precipitation anomaly over northern Europe including the BE region, thus suggesting a close association between the multidecadal variations of C-E European SATs and BE precipitation in summer.…”
Section: Introductionsupporting
confidence: 63%
“…Previous studies suggested that the AMV affects European summer climate (e.g. Sutton and Hodson 2005;Sutton and Dong 2012;Robson et al 2012;Müller et al 2014). The observed differences between the warm phase and the cold phase of the AMV have shown warmer summer SATs over C-E Europe to be associated with a warm phase of the AMV and vice versa (Sutton and Hodson 2005;Sutton and Dong 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such events are rare, and may be viewed as ''surprises''; arguably it is the importance of providing advanced warning of such surprises that motivates the need for a decadal prediction system. Examples of such events include the 1976 Pacific ''climate shift'' (Trenberth and Hurrell 1994;Meehl et al 2009Meehl et al , 2010, the rapid cooling of the North Atlantic Ocean in the 1960s (Thompson et al 2010), and the rapid warming of the North Atlantic in the mid 1990s (Robson et al 2012). The case study approach in the validation for decadal prediction systems is an important complement to overall metrics of skill, such as those proposed in this framework.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…7). We calculate the heat budget for the entire water column, similar to the approach from Robson et al (2012a) and unlike Yeager et al (2012), who have only accounted for the upper 275 m in their budget analysis. The heat budget is then the sum of net heat flux at the ocean-atmosphere interface (surface heat flux) and heat flux in the interior ocean due to advection and mixing of temperature at lateral boundaries (ocean heat flux).…”
Section: Heat Budget In the Subpolar Gyrementioning
confidence: 99%